Genomic And Physiological Characterisation Of Selected Arctic, Temperate And Tropical Pseudanabaena Strains - Khan, Zoya (2019)
Three filamentous cyanobacteria strains obtained from the High Arctic Svalbard archipelago, temperate (England) and tropical (Malaysia) regions were characterized using combined phenotypic and genetic approaches. Morphological and ultrastructural observations were performed together with growth measurements. Cell dimensions, thylakoid arrangement and apical cell shape of the Arctic and temperate strains were consistent with the description of Pseudanabaena catenata while the tropical strain was identified as Pseudanabaena amphigranulata. 16S rRNA gene analysis showed that the Arctic strain USMAC16 and temperate strain NIVA-CYA146 shared high sequence similarity (100% and 98%, respectively) with P. catenata SAG 1464-1. The tropical strain USMAC18 shared only 94% sequence similarity with Pseudanabaena sp. PCC 6802, suggesting that the strain is distinctly different from the strains currently available in the databases. All three strains showed identical internal transcribed spacer (ITS) configuration with other strains of Pseudanabaena. Cultures of each strain were exposed to various temperature and photoperiod treatments in order to examine phenotypic plasticity. The maximum cell length of Arctic and temperate strains (5.92±0.7 pm and 5.79±0.26 pm, respectively) was observed at 15°C culture temperature, and that of the tropical strain (5.7±0.07 pm) was at 25°C, all under 12L:12D hours (L: light, D: dark) photoperiod.